2001
DOI: 10.1117/12.432665
|View full text |Cite
|
Sign up to set email alerts
|

Applications of dielectric elastomer actuators

Abstract: Dielectric elastomer actuators, based on the field-induced deformation of elastomeric polymers with compliant electrodes, can produce a large strain response, combined with a fast response time and high electromechanical efficiency. This unique performance, combined with other factors such as low cost, suggests many potential applications, a wide range of which are under investigation. Applications that effectively exploit the properties of dielectric elastomers include artificial muscle actuators for robots; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
102
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(103 citation statements)
references
References 5 publications
0
102
0
1
Order By: Relevance
“…If the film is incorporated into a compliant frame with appropriate preloading, as shown in Figure 10, the film's orthogonal expansion can be converted into useful mechanical work. Linear strains of approximately 200% are possible with such a design [14]. When compared to conventional DC motor/gearhead combinations, dielectric elastomer actuators contain 10 to 100 times fewer parts.…”
Section: Dielectric Elastomer Actuatorsmentioning
confidence: 95%
“…If the film is incorporated into a compliant frame with appropriate preloading, as shown in Figure 10, the film's orthogonal expansion can be converted into useful mechanical work. Linear strains of approximately 200% are possible with such a design [14]. When compared to conventional DC motor/gearhead combinations, dielectric elastomer actuators contain 10 to 100 times fewer parts.…”
Section: Dielectric Elastomer Actuatorsmentioning
confidence: 95%
“…Under activation with a high DC voltage (kV ), the electrostatic pressure squeezes the elastomer film in thickness and thus, the incompressible film expands in planar directions. By properly configuring the DE actuator, the three-dimensional deformation of the film can be transferred into axial, 23,24 bending and radial motion. As shown in Fig.…”
Section: Miniature Spring Roll Dielectric Elastomer Actuatorsmentioning
confidence: 99%
“…Stanford Research Institute (SRI) [8] demonstrated some configurations of linear actuators, such as bowtie, push-pull, spider, tube, roll, etc. PLANTE, et al [9] , studied the diamond DEA, which had linear displacement of 22 mm.…”
Section: Introduction *mentioning
confidence: 99%